Facets of Urban Public Space: A study of V4 market streets of Chandigarh - Kanika Bansal; Harveen Bhandari (International Journal of Advanced Science and Technology, 2020)
Public spaces act as the crucial breathing spaces in urban cities with market streets as one of the most popular and vital urban public spaces on which the city life throngs. Due to the society’s rapid transformations mall culture is overriding the market streets, the essential day to day social interaction spaces. The societal, economic and technological pressures rising from the needs of 21st century, have become a large threat leading to imminent reduction of these quality public spaces. The current paper presents a study of V4 Market Street of Chandigarh, India a significant example of planned urban cities developed on a neighbourhood concept. Sector 22 market street, the first sector to be developed in the city, has been selected as it is a prime cultural, social and economic hub with deep-seated historical associations and a sense of identity based on its unique architectural character. The methodology adopted includes site surveys, questionnaire survey, direct and participant observation along with interviews held on site to be able to find factual issues. The various facets of market street have been analysed to bring to light the issues that are leading to deterioration of these urban public spaces and collapse of public realm in future.